DIVERSIFIKASI KURIKULUM DAN PEMBELAJARAN SELAMA PANDEMI COVID-19 DI SEKOLAH DASAR - Mariati Purba; Evi Sopandi; Slamet Wibowo (Akademika, 2023)
This research is motivated by the fact that during the COVID-19 pandemic learning in elementary schools faced many problems. First, curriculum targets have yet to be achieved; second, distance learning is complex, faces complex issues, and requires careful preparation. Based on Law Number 20 of 2003 concerning the National Education System, the government gives authority to schools to design a diversified curriculum and diffrerentiated instruction considering various conditions. This study aims to find information about the efforts of schools and stakeholders regarding implementing curriculum diversification and differentiation learning in elementary schools. The method is qualitative data collected through questionnaires throughout Indonesia, followed by interviews and discussions representing the population determined purposively. The research results show that many stakeholders need to understand government policies regarding curriculum diversification. Therefore, schools try to meet all curriculum demands uniformly. This study recommends that the government develop a pocketbook or handbook containing SOPs for various curricula and instructions during special conditions. In addition, supervision of schools needs to be carried out so